World Report on Disability: analysis of the disability issues and contributions of physical medicine and rehabilitation medical specialty in Turkey - AKYÜZ, GÜLSEREN DERYA (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2022)
World Report on Disability was prepared to facilitate the implementation of the United Nations Convention on the Rights of Persons with Disabilities which puts forward the requirement of full and effective participation of people with disabilities in the society as a human rights issue. The Report indicates concrete steps at international and national levels to achieve this goal. The aim of this paper is to analyse the situation in Turkey with regard to disability in relation to underlined concepts and recommendations in the World Report on Disability and to emphasise the already available and potential contributions of Physical Medicine and Rehabilitation medical specialty in the implementation of this Report at the national level.
Keywords: Disability; physical medicine and rehabilitation; Turkey; World Report on Disability; INTERNATIONAL CLASSIFICATION; HUMAN-RIGHTS; HEALTH